2022
DOI: 10.1155/2022/3961317
|View full text |Cite
|
Sign up to set email alerts
|

Study on Acoustic Emission and Damage Mechanical Properties of Freeze-Thaw Sandstone under Uniaxial Compression

Abstract: The damage strength of freeze-thaw rock provides an important reference for stability evaluations used during rock engineering in cold regions. In this paper, real-time acoustic emission tests of saturated sandstone are performed after various freeze-thaw cycles to study the uniaxial compressive strength and deformation characteristics of the resulting materials. The macro-meso damage evolution law of loaded sandstone is studied under the action of freeze-thaw cycles. The results show the following: (1) The sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Due to the lack of free expansion space, the water in the sandstone pores produces a large frost-heaving force during the freezing process. Due to the different initial saturations, the formation and development degree of ice and the frost heave force of water are different under freezing conditions, and the degree of frost heave damage in the internal structure of rock samples is different [ 28 ]. When the saturation is low, the damage effect of water on rock is mainly chemical softening, and the frost-heaving effect of water is weak, so the damage effect of water on rock is limited.…”
Section: Physical and Mechanical Properties Of Sandstone Under Freeze...mentioning
confidence: 99%
“…Due to the lack of free expansion space, the water in the sandstone pores produces a large frost-heaving force during the freezing process. Due to the different initial saturations, the formation and development degree of ice and the frost heave force of water are different under freezing conditions, and the degree of frost heave damage in the internal structure of rock samples is different [ 28 ]. When the saturation is low, the damage effect of water on rock is mainly chemical softening, and the frost-heaving effect of water is weak, so the damage effect of water on rock is limited.…”
Section: Physical and Mechanical Properties Of Sandstone Under Freeze...mentioning
confidence: 99%
“…[31] through the accumulative ring-down count during unconfined compression test, showed that soil damage was characterized by ringing AE count by analyzing the variation relation between AE parameters and stress. Liang et al [32] manifested that the cumulative ring count of sandstone gradually changed from the jumping stage to gradual growth with repeated F-T cycles. The AE characteristic parameters and ring count reflected damage of F-T sandstone.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they also analyzed the AE spectra and concluded that the high amplitude-low frequency signals were best for predicting brittle fracture. Liang et al 30 conducted AE tests on saturated sandstone after freeze‒thaw cycles and found that the higher the number of freeze‒thaw cycles, the shorter the time it takes for the rock to reach the accumulated damage threshold. Wang et al 31 studied the deterioration properties of rocks with the help of AE technology and found that the AE event rate of sandstone gradually changed from the "V" type to the "U" type.…”
Section: Introductionmentioning
confidence: 99%